Compensation of irrigation professionals: a comparative study of the Philippines, Sri Lanka and Pakistan - Kikuchi, M; Merrey, Douglas J.; Dassenaike, L. (International Water Management Institute, 2000)
This paper analyzes trends in the level of compensation of irrigation engineers in three irrigation agencies in three countries, Philippines, Sri Lanka, and Pakistan. The paper tries to relate these trends to the performance of the agencies, to understand promotion policies and their relationship to performance and compensation, and to compare the current level of irrigation engineers' compensation to that in other professions. In the Philippines and Sri Lanka, irrigation engineers' compensation has declined continuously, reaching a 1995 low that is one half of what they received in 1965 in real terms. Irrigation engineers' compensation in these countries was also considerably less than for engineers working in private firms and even in other government agencies. In contrast, irrigation engineers in one Pakistani agency have enjoyed a significant increase in their compensation, largely because of the high level of benefits. Trends in the performance of the three agencies studied showed a strong positive correlation with the trends in engineers' compensation, suggesting the plausibility of a relationship but not proving it. The study found that none of the agencies maintains adequate long-term records (two agencies were dropped from the study because the data were not adequate). The crudeness of the data and the analysis is such that no causal relationship is established, but there is a plausible case that compensation of irrigation professionals needs to be increased as part of a program to increase irrigation agency performance in developing countries.